Syntheses and structural properties of bis(hexacarbonyldicobalt) complexes from cyclic diynes - Rausch, Bernhard J.; Gleiter, Rolf; Rominger, Frank (Dalton transactions, 2002)
The bis(hexacarbonyldicobalt) complexes of nine ten- to fourteen-membered cyclic diynes (1-3, 5, 6, 8 and 10-12) have been isolated. The structural parameters of the complexes have been examined by means of X-ray investigations on single crystals. It was found that the chair like conformation of the uncomplexed rings is changed into a twisted one upon complexation. In addition to the pure hydrocarbons the syntheses of the bis(hexacarbonyldicobalt) complexes of eight heterosubstituted cyclic diynes (4, 7, 9, 13, 15-17) and of a mono(hexacarbonyldicobalt) complex 18 are reported and their structural parameters are presented.
Gesehen am 03.11.2020